Determination of Corporate Social Responsibility Disclosure Using Firm Size as a Moderation Variable in Palm Oil Companies - Yunarti, Yunarti; Erlina, Erlina; Fachrudin, Khaira Amalia (Journal of Social Science, 2023)
-